Iqaluit gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series ... - Anawak, Jack; Avva, Salome; Bonin-Labelle, Geneviève; Crawford, Anne; D'Argencourt, Madeleine; De Wolffe, Charlotte; Grenier, Claude; Guistini, Sean; He, Fanny; Hickes, George; Nagel, Patrick; Redfern, Madeleine (My University, 2017)
A collection of documents, audio recordings, and programming resulting from the second gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series held in Iqualuit, Nunavut on April 12th, 2017. ...